If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 4w = 6w + 9 Reorder the terms: -9 + 4w = 9 + 6w Solving -9 + 4w = 9 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. -9 + 4w + -6w = 9 + 6w + -6w Combine like terms: 4w + -6w = -2w -9 + -2w = 9 + 6w + -6w Combine like terms: 6w + -6w = 0 -9 + -2w = 9 + 0 -9 + -2w = 9 Add '9' to each side of the equation. -9 + 9 + -2w = 9 + 9 Combine like terms: -9 + 9 = 0 0 + -2w = 9 + 9 -2w = 9 + 9 Combine like terms: 9 + 9 = 18 -2w = 18 Divide each side by '-2'. w = -9 Simplifying w = -9
| -2.5p+2=0.2p+11 | | 114.95=39.95x | | x=0.29(10)+2.07 | | P^2+3p-56=0 | | 3/10*x=13-x | | 9x+12+3x=4x-8-12 | | 1/n^2-n-2 | | 10-3y=-7y-10 | | 7=8+y | | t(x)=5x^2+4x | | 1=-4+4m+5 | | 4v+8=6(v+4) | | 114=39.95x | | 12x-6-6x-8=4-3x | | 5(3x-10)-5x=-15 | | 39=-3v | | 21x+3d=45 | | 7y^2-y+2=0 | | 19y-10=11y-2 | | 6.4=1.3-0.7y | | X+67+x+127=180 | | 36-7b=-3b(8b+5) | | 2y-3y+5y=42 | | 5h+4=3h+8 | | -54=9x | | 5m+4=-26 | | X^2/x-5 | | 5h+4=h+8 | | 11=x-12 | | 88+2x+62=2x+26 | | 4/(x-2)=6 | | 1.1x-3x=-34.3 |